100-My history of bornavirus infections hidden in vertebrate genomes - Kawasaki, Junna; Kojima, Shohei; Mukai, Yahiro; Tomonaga, Keizo; Horie, Masayuki (Proceedings of the National Academy of Sciences - PNAS, 2021)
Although viruses have threatened our ancestors for millions of years, prehistoric epidemics of viruses are largely unknown. Endogenous bornavirus-like elements (EBLs) are ancient bornavirus sequences derived from the viral messenger RNAs that were reverse transcribed and inserted into animal genomes, most likely by retrotransposons. These elements can be used as molecular fossil records to trace past bornaviral infections. In this study, we systematically identified EBLs in vertebrate genomes and revealed the history of bornavirus infections over nearly 100 My. We confirmed that ancient bornaviral infections have occurred in diverse vertebrate lineages, especially in primate ancestors. Phylogenetic analyses indicated that primate ancestors were infected with various bornaviral lineages during evolution. EBLs in primate genomes formed clades according to their integration ages, suggesting that bornavirus lineages infected with primate ancestors had changed chronologically. However, some bornaviral lineages may have coexisted with primate ancestors and underwent repeated endogenizations for tens of millions of years. Moreover, a bornaviral lineage that coexisted with primate ancestors also endogenized in the genomes of some ancestral bats. The habitats of these bat ancestors have been reported to overlap with the migration route of primate ancestors. These results suggest that long-term virus–host coexistence expanded the geographic distributions of the bornaviral lineage along with primate migration and may have spread their infections to these bat ancestors. Our findings provide insight into the history of bornavirus infections over geological timescales that cannot be deduced from research using extant viruses alone, thus broadening our perspective on virus–host coevolution.